Magnesium pentahydridocobalt (I) - S.F.Parker, ISIS (My University, 1998)
Inelastic Neutron Scattering spectrum of Magnesium pentahydridocobalt (I), Mg₂COH₅, measured on the TFXA instrument.
Keywords: TFXA